Pengaruh Fanatisme Terhadap Agresi Verbal Suporter Timnas Indonesia di Media Sosial : Penelitian - Eko Alwinasirin; Rizky Putra Santosa (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to find out whether fanaticism affects verbal aggression shown by Indonesian national team supporters on social media. The background of this research is the rise of negative and attacking comments directed at players, coaches, and even PSSI officials, especially after Indonesia lost to China and failed in the 2024 AFF Championship. This situation shows signs of aggressive behavior caused by disappointment over the match results. The subjects of the study were 92 supporters who actively follow the progress of the national team and have posted negative comments on social media. Data were collected using Verbal Aggression and Fanaticism measurement tools. The regression analysis showed no significant relationship between fanaticism and verbal aggression (p > 0.05, R² = 0.001). These findings suggest that other factors, such as personality, self-control, and social pressure, may have a stronger influence on verbal aggression. The researcher recommends adding other variables besides fanaticism in future studies for better results.